Անգլերեն և հայերեն ֆինանսաբանկային տերմինաբանության իմաստակառուցվածքային վերլուծության հարցեր - A. Saroukhan
В постсоветской Армении банковское дело бурно развивалось. До этого, будучи ограниченной правилами советской плановой экономики, самостоятельная банковская и финансовая терминологическая система не была сформирована. В формировании подобной системы важную роль сыграли калькирование, перевод и заимствование английской терминологии. Путем сопоставления английских и армянских финансово-банковских терминов можно выявить 15 структурно-семантических моделей, которым и посвящена данная статья.In post-Soviet Armenia the banking and finance sector underwent a rapid growth. Prior to it being trapped by the Soviet planned economy the terminology o f banking and finance in Armenian had not been sufficiently developed. Caiques, translation, and borrowings are of significant importance in the process of formation of aforementioned terminology. The article focuses on the contrastive analysis of English and Armenian banking and finance terms which allows to reveal fifteen semantic and structural models.
Keywords: Լեզվաբանություն; Քերականություն